Maintaining a Sufficient and Quality Physician Workforce: The Role of For-profit Medical Schools - Jessica M. Babcock; Blake D. Babcock; Marshall Z. Schwartz (SAGE Publishing, 2013)
Currently, in the United States there is a significant physician workforce shortage. This problem is likely to persist as there is no quick solution. The nature of this shortage is complex and involves factors such as an absolute physician shortage, as well as physician shortages in primary care and certain specialty care areas. In addition, there is a misdistribution of physicians to medically underserved areas and populations. The medical education system trains medical school graduates that eventually feed the physician workforce. However, several factors are in place which ultimately limits the effectiveness of this system in providing an appropriate workforce to meet the population demands. For-profit medical schools have been in existence in and around the continental US for many years and some authors have suggested that they may be a major contributor to the physician workforce shortage. There is currently one for-profit medical school in the US, however the majority exist in the Caribbean. The enrollment in and number of these schools have grown to partially meet the ever-growing demand for an increase in medical school graduates and they continue to provide a large number of graduates who return to the US for postgraduate medical training and, ultimately, increase the physician workforce. The question is whether this source will benefit the workforce quality and quantity needs of our growing and aging population.